Carbon Sinks of Steel: Using Bamboo to Combat Climate Change - Kirchhof, Erica (Consilience, 2021)
According to the United States Environmental Protection Agency, conventional agriculture accounts for approximately 19-29 percent of greenhouse gas emissions worldwide—a proportion destined to increase with the rising world population. As a result, it is important to uncover areas where methods of sustainable agriculture can be implemented or improved, and fostering these opportunities in the agricultural communities of developing nations offers great potential for reducing international greenhouse gas emissions. For many areas of the world, one promising strategy can be found in the cultivation of bamboo. A perennial plant within the grass family (Poaceae), bamboo belongs to the subfamily Bambusoideae and consists of over 1500 known species in approximately 119 genera. Although endemic to nearly every continent, the greatest species diversity of bamboo can be found in the subtropical regions of Asia, Africa, and Latin America. This paper aims to examine the cultivation of bamboo in rural communities and developing nations as a strategy of climate change mitigation and land revitalization. The potential of bamboo to be used in international carbon trading schemes is also analyzed. As an agriculturally relevant crop for many remote communities, the cultivation and harvest of bamboo can provide a meaningful source of income to developing areas while also helping nations meet sustainability and emissions reduction goals.